RESEARCH ON THE QUALITY OF HONEY AND POLLEN OBTAINED DURING THE BEEKEEP FROM BOIAN VILLAGE SIBIU COUNTY, ROMANIA, IN VIEW OF THE ECOLOGICAL CERTIFICATION OF BEEKEEPING PRODUCTS - George MOISE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present paper aimed to perform instrumental analyzes on actual hive products: six varieties of honey and three varieties of pollen, extracted from the apiary in the village of Boian, Bazna commune, Sibiu county, in order to certify them as organic products. The hive consists of 130 bee families, the form of beekeeping is stationary and pastoral. The type of crates is 90% of the vertical Dadant type, and the remaining 10% of the horizontal Dadant type. Bee families benefit from adequate microclimate conditions and care. The geographical factors and the honey base in the village of Boian, but also the pastoral movement make possible the good functioning of the apiary and to obtain important incomes following the beekeeping activity. In order to ecologically certify the bee farm, the following conditions are met: the apiary is well organized and has been operating for 25 years and can be reconverted from conventional apiary to organic apiary, there is an ecological honey base in the areas where the harvest is done, environmental conditions are optimal in the village of Boian, and the bees benefit from organic hives and quality ecological food in winter.